(untitled) (Journal of actual problems of jurisprudence, 2018)
In article the concept and the legal nature of amnesty – the extrajudicial deed of release from criminal liability and punishment are considered. The author reveals features of application of the act of amnesty to the citizens who are subject to granting of amnesty. The concept, essence and features of application of the act of amnesty are analyzed. And also, the attention is focused on differentiation of the act of amnesty and pardon. Key words: crime, release from criminal liability, release from punishment, regulatory legal act, bill, criminal liability, punishment, act of amnesty, pardon.